Roles and mechanisms of biomechanical-biochemical coupling in pelvic organ prolapse - Wu, Huaye; Zhang, Ling; He, Li; Lin, Wenyi; Yu, Bo; Yu, Xia; Lin, Yonghong (Frontiers in Medicine, 2024)
Pelvic organ prolapse (POP) is a significant contributor to hysterectomy among middle-aged and elderly women. However, there are challenges in terms of dedicated pharmaceutical solutions and targeted interventions for POP. The primary characteristics of POP include compromised mechanical properties of uterine ligaments and dysfunction within the vaginal support structure, often resulting from delivery-related injuries. Fibroblasts secrete extracellular matrix, which, along with the cytoskeleton, forms the structural foundation that ensures proper biomechanical function of the fascial system. This system is crucial for maintaining the anatomical position of each pelvic floor organ. By systematically exploring the roles and mechanisms of biomechanical-biochemical transformations in POP, we can understand the impact of forces on the injury and repair of these organs. A comprehensive analysis of the literature revealed that the extracellular matrix produced by fibroblasts, as well as their cytoskeleton, undergoes alterations in patient tissues and cellular models of POP. Additionally, various signaling pathways, including TGF-β1/Smad, Gpx1, PI3K/AKT, p38/MAPK, and Nr4a1, are implicated in the biomechanical-biochemical interplay of fibroblasts. This systematic review of the biomechanical-biochemical interplay in fibroblasts in POP not only enhances our understanding of its underlying causes but also establishes a theoretical foundation for future clinical interventions.